OMNIgene.SPUTUM for transporting sputum in ambient temperature for tuberculosis testing: Bangladesh experience - Senjuti Kabir; Sabrina Choudhury; Mohammad Khaja Mafij Uddin; M.D. Fahim Ather; Syed Mohammad Mazidur Rahman; Pronab Kumar Modak; Mohammad Samsuddoha Sarker Shanchay; Tanjina Rahman; Shahriar Ahmed; Sayera Banu (Journal of Clinical Tuberculosis and Other Mycobacterial Diseases)
Background: Performance of OMNIgene.SPUTUM (OM-S) for transporting sputum was evaluated. Methods: This exploratory study was conducted during January-December 2019 at four near and one distant healthcare-facilities of Dhaka. Smear-positive pulmonary TB patients’ sputa were collected, divided into ‘OM-S untreated’ and ‘OM-S treated’ portions, and transported to testing laboratory, Dhaka, on same-day from near-sites, and through courier from distant-site for smear-microscopy, culture, and Xpert MTB/RIF (Xpert) testing. Subset of ‘OM-S treated’ sample was tested with Xpert without centrifugation. Test results of all portions were compared in between. Results: Total 444 participants were enrolled (near-sites:198, distant-site: 246). All test results were comparable in both portions for near-sites. For distant-site, smear-microscopy’s positivity was reduced by 4.1 % in ‘OM-S treated’, Xpert showed 100 % concordance in both portions, and culture was higher in ‘OM-S treated’ than ‘OM-S untreated’ (92.3 % vs 89.4 %; p = 0.288). Primary contamination rate in ‘OM-S treated’ was lower than ‘OM-S untreated’ (2.0 % vs 9.8 %; p < 0.05). For all sites, median (IQR) time-to-culture positivity was 35 (28, 42) days in both portions. Xpert positivity was 99 % concordant in ‘OM-S treated’ regardless of centrifugation. Conclusions: OM-S is safe for sputum transportation. OM-S mixed sputum can be tested with Xpert and culture. Further studies can validate findings and assess cost-effectiveness.